Pengaruh Transparansi dan Akuntabilitas terhadap Kinerja Pengelola Zakat dengan Jenis Lembaga Sebagai Moderasi - Denta Safitri; Alim Erdiansah; Aidil Novia; Hulwati Hulwati (Ekonomis: Journal of Economics and Business, 2026)
The purpose of this study was to examine how transparency and accountability affect the performance of zakat managers with the type of institution as a moderating variable. The population in this study were muzaki at Baznas Padang City and Lazismu Padang City. The sample size used Hair's formula which resulted in a sample size of 200. The sampling technique used purposive sampling and the analysis technique used SEM (Structural Equation Model) with Smart-PLS. The results of this study indicate that there is one direct effect test whose results are positive and significant, namely: Transparency has a positive and significant effect on Zakat Management Performance, while Accountability has a positive but insignificant effect on Zakat Management Performance. The results of the influence test with moderating variables show that the Type of Institution strengthens the relationship between Transparency and Zakat Management Performance but is not significant.